IMPLIKASI PERSONNEL DAN CULTURAL CONTROL TERHADAP MOTIVASI INTRINSIK ABDI DALEM PUNOKAWAN DI KRATON JOGJAKARTA - Meilana Meilana (CALYPTRA, 2019)
ABSTRACT The control system must be well designed by the business entity so that the objectives of the business entity for the short and long term can be achieved. A good control system is proactive rather than reactive. Control alone can be divided into four kinds of action control (action control), result control (control), personal control (personnel control), and cultural control (cultural control). This thesis contains research on the implications of personnel and cultural control on intrinsic motivation of Abdi Dalem Punokawan in Kraton Jogjakarta. In this thesis disclosed about the very high level of motivation of the work of the Abdi Dalem in the palace, which is caused by the implementation and implementation of appropriate personnel and cultural control system. The Abdi Da lem has a working motivation because Kraton Jogjakarta has a good personnel and cultural control system. Where this control has a direction that tends to approach intrinsic motivation. In accordance with the purpose of the study of this thesis, in the discussion will be seen how the implications of personnel and cultural control to build intrinsic motivation of the Abdi Dalem Punokawan in Kraton Jogjakarta. Keywords: personnel control, cultural control, Abdi Dalem Punokawan, motivation 3.0 ABSTRAK Sistem pengendalian harus dirancang dengan baik oleh badan usaha sehingga tujuan badan usaha untuk jangka pendek dan jangka panjang dapat tercapai. Sistem pengendalian yang baik adalah yang bersifat proaktif bukan reaktif. Pengendalian sendiri dapat dibagi atas empat macam yaitu pengendalian tindakan (action control), pengendalian hasil (result control), pengendalian personal (personnel control), dan pengendalian kultural (cultural control). Skripsi ini berisi penelitian mengenai implikasi personnel dan cultural control terhadap motivasi intrinsik Abdi Dalem Punokawan di Kraton Jogjakarta. Dalam skripsi ini diungkapkan mengenai sangat tingginya tingkat motivasi kerja para Abdi Dalem di Kraton, yang disebabkan oleh penerapan dan pelaksanaan sistem personnel dan cultural control yang tepat. Para Abdi Dalem memiliki motivasi kerja karena Kraton Jogjakarta memiliki sistem pengendalian personnel dan cultural control yang baik. Dimana pengendalian ini mempunyai arah yang cenderung pada pendekatan motivasi intrinsik. Sesuai dengan tujuan studi penulisan skripsi ini, dalam pembahasannya akan dilihat bagaimana implikasi personnel dan cultural control untuk membangun motivasi intrinsik para Abdi Dalem Punokawan di Kraton Jogjakarta. Kata kunci: personnel control, cultural control, Abdi Dalem Punokawan, motivasi 3.0